2021
DOI: 10.12998/wjcc.v9.i11.2487
|View full text |Cite
|
Sign up to set email alerts
|

Differences in dietary habits of people withvswithout irritable bowel syndrome and their association with symptom and psychological status: A pilot study

Abstract: BACKGROUND Previous studies have demonstrated that dietary factors are involved in irritable bowel syndrome (IBS), but the role of diet was evaluated mostly based on food frequency questionnaire. Whether food categories, quantity per time, and intake frequency are different between IBS patients and non-IBS individuals has not been clearly clarified. AIM To explore differences in dietary habits of people with vs without IBS and their correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Studies have shown that high‐frequency consumption of seafood decreases the risk of cardiovascular disease mortality, 31 diabetes mellitus, 32 inflammatory diseases, 33 cancers like gastrointestinal cancers 34 and prostate cancer 35 . However, the association between seafood and IBS has been poorly studied, and a study performed by Meng et al 36 found only intake of seafood differed between patients with and without IBS in quantity per time, and no evidence of a relationship was found between them. Nowadays, there remains a lack of research on the causal associations between seafood preference and health outcomes, and our study was the first to reveal that preference for seafood like salmon could be a protective factor for IBS, while sardine‐liking was suggested to be a risk factor, the specific mechanisms should be explored further by more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high‐frequency consumption of seafood decreases the risk of cardiovascular disease mortality, 31 diabetes mellitus, 32 inflammatory diseases, 33 cancers like gastrointestinal cancers 34 and prostate cancer 35 . However, the association between seafood and IBS has been poorly studied, and a study performed by Meng et al 36 found only intake of seafood differed between patients with and without IBS in quantity per time, and no evidence of a relationship was found between them. Nowadays, there remains a lack of research on the causal associations between seafood preference and health outcomes, and our study was the first to reveal that preference for seafood like salmon could be a protective factor for IBS, while sardine‐liking was suggested to be a risk factor, the specific mechanisms should be explored further by more studies.…”
Section: Discussionmentioning
confidence: 99%